Du Ferlo au Bassin arachidier (Sénégal) : analyse de la composition floristique de la végétation envisagée comme ressource et comme indicatrice des changements socio-environnementaux - Ababacar Fall (Physio-Géo)
The evolution of the biophysical characteristics of the African Western Sahelian environment and the Senegalese Ferlo in particular is marked by strong fluctuations in the rainfall intervened during these last decades and which had important consequences on the biological potential of the region. The modifications that they have induced on the ecosystems are read through the floristic composition, the chorology of species found in the region and the contours of the landscapes; flora is a good indicator of the biophysical environment evolution during the last decades. So the phytoclimatic organization at the micro-regional scale deserves to be reviewed and updated in light of major changes. The floristic study of plant resource, seen through the prism of dual anthropogenic practices and changing environmental conditions, allows to understand better the complexity of the internal physical and societal dynamics.